EFL TEACHERS’ PERSPECTIVES ON MOBILE-ASSISTED LANGUAGE LEARNING (MALL) RESOURCES FOR VOCATIONAL HIGH SCHOOL STUDENTS - Nara Sari; Teguh Sulistyo (UIBU, 2022)
This study aimed to ascertain vocational EFL teachers’ perspectives on the development of Mobile-Assisted Language Learning (MALL) resources in vocational schools. It employed a mixed-method approach in which data were collected simultaneously using an open-ended questionnaire and semi-structured interviews. The study involved 95 English teachers from vocational schools in two cities of East Java, Indonesia. Among the participants, four were invited to participate in an online interview to discuss their perspectives on the characteristics, use and development of MALL material for vocational students. Data analysis was performed using descriptive statistics. The analysis results showed that more than half of the respondents agreed that MALL resources were more accessible (65.4%), easier to generate (65.4%) and more successful at improving learners’ autonomy (73.1%), compared to traditional materials. Additionally, 40% of teachers thought that MALL materials could be used to promote classroom interaction, and it was much easier for teachers to provide immediate feedback through mobile phone. In summary, 42% of teachers agreed that MALL resources could aid in foreign language acquisition. Due to students’ proximity to technology and mobile devices, teachers recognized that MALL materials can be applied inside and outside the classrooms. Therefore, vocational EFL teachers must be able to develop and implement MALL materials in their classrooms.